Vacancy formation enthalpy in CoCrFeMnNi high-entropy alloy. (February 2020) - Sugita, Kazuki; Matsuoka, Naoki; Mizuno, Masataka; Araki, Hideki
Abstract : In order to determine the vacancy formation enthalpy in a CoCrFeMnNi high entropy alloy, we have performed positron lifetime measurements over a temperature range from 293 to 1423 K. A vacancy formation enthalpy of 1.69 ± 0.13 eV was obtained using a threshold method, similar to the value of 1.72 ± 0.18 eV obtained using an Arrhenius plot. The vacancy formation energies are within the formation enthalpy ranges of the constituent pure metals. The vacancy diffusion activation energy of 2.78 ± 0.08 eV is in excellent agreement with the self-diffusion activation energies reported for the constituent face-centered cubic metals.